PENINGKATAN KEMAMPUAN BERPIKIR KRITIS DAN LOGIS MATEMATIK SISWA SMK MELALUI MODEL KOOPERATIF TIPE STAD BERBANTUAN MAPLE - maryanti maryanti (Universitas Syiah Kuala, 2019)
Critical and logical thinking is very important in the study of mathematics, as described in the 2013 curriculum that is currently implemented. However, this ability is often overlooked in the study of mathematics, which still adhered to the old paradigm that learning is less engaging students in active thinking. Thus, students are not used to empowering the cognitive function in thinking. This study aimed to determine the increase in students' critical thinking skills and logical-mathematical in learning mathematics through the cooperative model of Student Team Achievement Division (STAD) assisted Maple. This research used experimental method, with the control group pretest-posttest design. The population was all Year 10 classes in one of the vocational high schools in Banda Aceh, Indonesia. Two classes were taken as the sample (the experimental and control class) through a random sampling technique. Data collection was performed using the tests of critical thinking and logical-mathematical ability. T-test was conducted to see the difference in ability between groups of students learning with STAD and the conventional group, at a significance level of 0.05. The results showed that: 1) Improvement of critical thinking skills of students who got the mathematical learning of mathematics through STAD cooperative model-assisted Maple was better than the students who received conventional learning. 2) Improvement of logical-mathematical thinking ability of students who receive mathematics learning through cooperative model STAD assisted Maple was better than the students experienced the conventional learning.